A The Role of Functional Imperatives in Stimulating Carbon Management Accounting By Mediating Management Accounting in Waste Management - Prajogo, Budi; Murwaningsari, Etty; Mayangsari, Sekar (IJOSMAS, 2023)
Abstract. The aims of this research to examine and analyze the effect of Functional Imperatives (FI) on “Environmental Management Accounting” (EMA) and “Carbon Management Accounting” (CMA), as well as to analyze the indirect effect of FI on CMA mediated by EMA. This quantitative study performed hypothesis tests on the three variables, namely CMA (5 dimensions and 16 measurement indicators), EMA (3 dimensions, 10 subdimensions, and 43 indicators), and FI (3 dimensions with 15 indicators), where all measurements used a Likert scale of 1 to 7. Furthermore, the samples were collected using the purposive sampling technique with certain criteria, including stakeholders, namely the waste bank manager and the authorized government. The samples were 445 respondents with a requirement of at least 5 times the number of indicators (370 respondents). The analytical method used was SEM-PLS. The results showed the FI had a positive effect on EMA and CMA. Also, EMA is proven to have a positive effect on CMA and mediates the effect of FI on CMA.